(untitled) (Journal of the College of Basic Education, 2025)
Recently, there has been a renewed interest in reshaping the black identity before and after the American Civil War due to color discrimination, ideological and cultural beliefs between the white and the black people. In this research, reshaping the black identity from feminist critical discourse analysis, a contemporary sub-discipline of linguistics, presents a powerful tool in shaping and reshaping these beliefs in the most current trends in the language field and locates it among the available literature. The contribution of feminist critical discourse analysis has received little attention on black identity. The principal objective of this research is to investigate the development and transformation of blacks into literate human beings within Harper’s Lola Leory and how black women revolted to have their human rights equal to those of white women. This research provides a novel approach to the quantity and quality of the research results using a mixed method. An analytical and eclectic framework has been used: Woda and Reisigl’s discourse historical approach (2015) and Lazar’s (2014) feminist critical discourse analysis. The results have indicated that black people receive degrading treatment and poor living facilities in comparison with white people. However, the former takes action at the end and becomes equal, free, and literate like the latter. The feminist movement has also achieved its objectives in liberating the novel’s protagonist, as a clear indication of the liberation of all black women. The present results highlight the detrimental effects that ideology and ethnicity play a pivotal role in reshaping the lives of people, and especially have a strong influence on the ’Others.’